Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 1668103614 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "TaxonKey is Animalia" ] } The dataset includes 1668103614 records from 25965 constituent datasets: 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 7956 records from Finds of rare species of animals in Ukraine (2022). 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 6 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 1 records from Inventory of plant species through Benin (West Africa). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 3105 records from South Caribbean Diversity. 6264 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 876 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 85 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 139 records from Bannwald Burghauser Forst. 66 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Amphibien - POPAmphibien. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 948 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 290 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 24 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 2011 records from UNCW Right Whale Aerial Surveys 2008. 65 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 19021 records from University of Guam Insect Collection. 240 records from Pollen record of sediment core Bokanjacko Blato 1. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 15 records from Artenvielfalt des "Grünen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 6 records from Hydromedusae observed during night dives in the Gulf Stream. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 59 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 1189 records from UWIZM Molluscs. 4083 records from MCP-Aves - Coleção de Aves. 13 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 975 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 6 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 1514 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 1 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 2 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2926 records from Collections of Bioclass, school #179, Moscow. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 104 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement de la commune de Chepnier. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 1818 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1688 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 4 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 51 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 86237 records from Marine Offshore Seabed Survey data held by JNCC. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 280 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 249 records from Fermanagh Flora. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 78 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 15 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 8 records from The InBIO Barcoding Initiative Database: Ypsolopha milfontensis, a new species from the Portuguese coast (Lepidoptera: Ypsolophidae). 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 17 records from Revision of the Oriental genus Horniella Raffray (Coleoptera, Staphylinidae, Pselaphinae). 490 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 4 records from A new species of crown-antlered deer Stephanocemas (Artiodactyla, Cervidae) from the middle Miocene of Qaidam Basin, northern Tibetan Plateau, China, and a preliminary evaluation of its phylogeny. 5 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 4 records from Diatom abundance of Hole 95-613. 377 records from Inventaires et suivis faune - Inventaire et suivi des libellules – Protocole STELI. 5 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 5194 records from Réseau de suivi des macro-invertébrés aquatiques - Inventaire et suivi Macroinvertébrés. 23 records from Abundance of benthos infauna at station GIK23042-2. 5 records from Streuobstwiese. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from On the taxonomy of Negeta semialba Hampson, 1918 with descriptions of two new Leucobaeta László, Ronkay & Witt, 2010 species (Lepidoptera, Nolidae, Nolinae). 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1012 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1461 records from M. Gollop Collection. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier DELZONS. 145 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 106 records from BIRDRACE Bon(n)apartemöwen. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4180 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 3 records from First description of the metopiine genus Trieces Townes, 1946 (Hymenoptera: Ichneumonidae) from the Indomalayan region with three new species from India. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 16 records from Insect Collections of Okomu National Park- Nigeria. 279489 records from ARABEL - Arachnologia Belgica. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 217 records from Heinersdorfer Sumpfwiese. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1005 records from Missisquoi National Wildlife Refuge Bumblebee (Bombus) Surveys. 409 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 7 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 174 records from Antarctic pycnogonids. 60970 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 150 records from Projet de transport par câble entre le Chaudron, Moufia et Bois de Nèfles - Oiseaux - inventaires. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 1519 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 386 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1294 records from Midden-Limburg Fish Ponds Survey. 171 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 1 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1803 records from AMAPPS Northeast Aerial Cruise Summer 2016. 903 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Geometridae de France métropolitaine. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1290 records from Diversity of Spiders from Azorean Trails. 13442 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 36449 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 69 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10283 records from Inventario de Hymenóptera; parasítica en México. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 94 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Oiseaux. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 27 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 117 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 3 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 85 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 20 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LE GLOANEC Vincent. 243739 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81, 1983-5. 5260 records from Whale catches in the Southern Ocean. 21 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 230 records from Biometría peces Parque Nacional Natural La Paya. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13864 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 53 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 18 records from Anfibios presentes en el Cerro Jánano. 26 records from Données espèces - Expertise IPE 79. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 420 records from Catalog of type specimens of the fish collection of the Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura (NUP), Universidade Estadual de Maringá Paraná, Brazil. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 114 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 83 records from Ostracoda abundance of Hole 48-403. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 2718 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Redescription of Nanomysis siamensis W. M. Tattersall, 1921 (Crustacea: Mysida) after 100 years, with an update of its distribution in the Songkhla Lagoon System southern Thailand. 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 13 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kathy FOOT. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Yves BOUTET. 1 records from Données des collections du MNHN - Données des collections d'algues du MNHN. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 406862 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Données Association Évasion tropicale (AET) - Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 456 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne d’investigations ichtyofaune – Ferme pilote de Groix & Belle-Ile. 118 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 16 records from Hazel Dormouse in Ireland. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1030 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 1 records from A new species of the genus Scincella (Squamata: Scincidae) from Yonagunijima Island, Southern Ryukyus, Japan. 33 records from An der Ohm, (Wettsaasen). 475 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Elaboration du DOCOB du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire des odonates d'intérêt communautaire. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 13 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 2112 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection de Hubert Piguet - Famille des Elateridae. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 12 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 3 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1539 records from Jurica-Suchy Nature Museum at Benedictine University Fossil Specimens (Arctos). 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 796 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire entomologique 2020 de la réserve biologique dirigée du Nord Grande Terre, Guadeloupe (ONF). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 3 records from On a collection of Scaphisomatini (Coleoptera: Staphylinidae: Scaphidiinae) from West Malaysia. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 2 records from Revision of the African cichlid fish genus Ctenochromis (Teleostei, Cichliformes), including a description of the new genus Shuja from Lake Tanganyika and the new species Ctenochromis scatebra from northern Tanzania. 34 records from Happywhale - Bryde's whale in South Atlantic Ocean. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 529 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Diversity en ecological features of Majidae crabs from Morrocoy National Park - Venezuela. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 11894 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 57 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68772 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 10 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Chauves-souris - Points d'écoute au sol. 256 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 18 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 539 records from Phenological Center - Birds (Murmansk). 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 392 records from Hawthorne Canal Birdwatching Survey. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 212 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 199 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 469 records from Grassland cartography SICONA, Recorder-Lux database. 14 records from A new species of Pristimantis Jiménez de la Espada, 1870 (Anura: Strabomantidae) from the “ Brejos de Altitude ” in Northeast Brazil. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LEFEBVRE François. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 18 records from Naturtag. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BLANC Josselyne. 251 records from Monitoring of colonial waterfowl species (2013-2014). 1004 records from Inventaire Odonates-Rhopalocères 1999-2002 du PNRLG - Données odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 169 records from Colección de Zoología Universidad Icesi: Mamíferos. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 1 records from Elaphoidella longiramus sp. nov. (Copepoda: Harpacticoida, Canthocamptidae), a new species of cave-dwelling copepod from central Thailand. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 39 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 7283 records from Colecção Entomológica IIA. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 2 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 16763 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 1211 records from Wintering wildfowl in Portugal – 1992-1993. 3 records from A new genus and two new species of Swordtail Crickets (Orthoptera: Trigonidiidae; Trigonidiinae) from China. 148 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 24 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 1188 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 64 records from Osoriinae of Cuba with description of new species and an identification key (Coleoptera: Staphylinidae). 21 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 5855 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4644 records from Données Association Évasion tropicale (AET) - Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 770 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 3568 records from Spatial and temporal ichthyofauna community of a tropical mangrove Bay (Gazi Bay, Kenya) sampled between 1994 and 1996. 1082 records from DMNS Egg Collection (Arctos). 35 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Anaïs MAS. 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 12 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 30 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 20 records from Flux data of NU2_trap (Table A1). 398 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 2851240 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from SILENE-FAUNE-PACA - ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 1 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Sediment metagenome. 13708 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 7124 records from Caracterización de fauna en diferentes gradientes altitudinales del departamento de Boyacá, Colombia. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 30 records from Happywhale - Blue Whale in Southern Ocean. 11586 records from Happywhale - Humpback Whale in North Atlantic Ocean. 849 records from CNAN/Scorpiones. 1519 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 778 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 820 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 151 records from Harpacticoid copepods in tropical seagrass beds of Gazi Bay (Kenya) and Mbweni (Zanzibar) sampled in July and August 1996. 184 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 92 records from Vespertilionidae. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 15440 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 355 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 470 records from 59 - Beau Gui Avifaune. 3089 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Mares. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 120 records from BIRDRACE The early birds. 2125 records from Regroupement d'études et d'inventaires - Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 82 records from Type locality records of Polycystididae species in the world. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1122 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Stéphane ORIO. 382 records from Collection Echinodermata - ZMB. 434 records from Inventario herpetofaunístico del noroeste de Hidalgo. 754 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 60 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 4 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 436 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 7 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 45 records from Plan de gestion 2007 - 2011 du site du Coteau de Peyroutet (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 6192 records from NE Scotland fish records 1800-2010. 69 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 35 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 40 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 92 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 144 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 94 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 57965 records from Fichier communal des ongulés. 33 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 43 records from Projet éolien de Saint-Barbant - Autre faune. 24 records from Caracterización de Mamíferos en el área de Farallones, jurisdicción de CORPOGUAVIO. 385 records from Eufáusidos norte de Chile. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 9257 records from Service National d'Observation CORAIL - Réseau de surveillance Polynesia Mana - Peuplements de poissons. 115 records from Living Cirripedia. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 1332 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Redescription of Paguristes aztatlanensis Glassell, 1937 and description of a new species of the genus Paguristes Dana, 1851 (Anomura, Paguroidea, Diogenidae) from western Mexico. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 6 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 5 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 218 records from Land and freshwater molluscs of Northern Spain. 6 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 3647 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Charlotte PICARD. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 9883 records from University of Nebraska State Museum Birds Collection. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 32169 records from University of California Santa Barbara Invertebrate Zoology Collection. 261 records from Seasonal variation of the zooplankton community at Gazi, Lamu and Malindi (Kenya) sampled between 1990 and 1992. 25025431 records from iNaturalist Research-grade Observations. 27 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 37 records from Bohemannia auriciliella (Nepticulidae) specimen data. 13 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 4882 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 1 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 36 records from Réseau Loup - Lynx ONCFS - Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 137 records from Hartland Nature Club Lepidoptera Collection. 114 records from BIRDRACE LiLaLau. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 95848 records from Fish specimens of Kagoshima University Museum. 3822 records from UTEP Invertebrates (Arctos). 217 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des odonates 2014. 1328 records from Fish occurrence in Kuban River basin. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 10 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 1422 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 18 records from Phase 2 Lowland Grassland Survey of Wales. 267172 records from hymenoptera. 5 records from Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species. 60 records from Amphibian and Reptilian (KIEE-AR). 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 81 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 1360131 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 413272 records from DATAVES. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 12 records from Analyses of the recent components of sediment core PS1011-1. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 30 records from MVZ Herp Observations (Arctos). 155 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 6 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Séverine VITRAT. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 45 records from Natterjack Toads of Ireland. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 20 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202114 records from National Benthic Inventory. 15 records from Plan de gestion 2016 - 2020 du site du domaine de Rodié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 16 records from Phenological Center - Fishes (Murmansk). 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 1 records from Plan de gestion 2018 - 2022 du site de la Butte de la Lot (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1293 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 2 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 196 records from Demospongias de la Laguna La Restinga, Venezuela. 167565 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 72 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations d'orthoptères (inventaire) réalisées par Locusta. 325642 records from Seasearch Marine Surveys in England. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 2913 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 90 records from Projet éolien - Insectes - Inventaire non protocolé. 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 608 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 78 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 47 records from Unter hellen Zinnen und finsteren Grotten. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2357 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 576 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 12 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Grand Voyeux - Suivis scientifiques. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 86 records from UWIZM Cnidarians. 243 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 14329 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 186451 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 2292 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 1 records from Discovery of a new species of Euphlyctis (Anura: Dicroglossidae) from the western coastal plains of peninsular India. 93421 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 30 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 17844 records from Chrysomelidae beetle data from iRecord. 1264 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) The Arctic University Museum of Norway. 60 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1828 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 56 records from Faunal assemblage of sediment core TR149-32. 790 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 125 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 2 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 1 records from First record of the freshwater crab genus Esanthelphusa Naiyanetr, 1994 (Decapoda: Brachyura: Gecarcinucidae) from Myanmar, with the description of a new species from the Kayin State. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 5 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 2 records from Revalidation and redescription of a gobionine species Microphysogobio bicolor (Nichols, 1930) (Teleostei: Cypriniformes) from the Yangtze River Basin, China. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 7 records from Disentangling the Pelodiscus axenaria complex, with the description of a new Chinese species and neotype designation for P. axenaria (Zhou, Zhang & Fang, 1991). 1656 records from Happywhale - Gray Whale in North Pacific Ocean. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 130427 records from Suivi Temporel des Rhopalocères de France (STERF). 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 2 records from Zapada (Plecoptera: Nemouridae), a stonefly genus new to the fauna of China. 187 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1587 records from Study of epifauna and meiobenthos by means of cage experiments in a Ceriops tagal and Avicennia marina mangrove at Gazi Bay (Kenya) in August and September 1992. 4 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 105 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 7 records from An overlooked case for a century: taxonomy and systematics of a new Iberian species of Eumerus Meigen, 1822 (Diptera, Syrphidae). 402 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de VINCENT Alexis (SAPROX). 27 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 51 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 2690 records from Gymnasium students as bat researchers. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1 records from Kohnometopus yasunagai sp. nov., (Hemiptera, Heteroptera, Miridae, Isometopinae) from Peninsular Malaysia. 448 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 97 records from WildesMoor bei Schwabstedt. 669 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 32 records from Antarctic Pycnogonids II. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 2 records from Potamophylax idliri sp. nov. (Trichoptera: Limnephilidae), a new species from the Jastrebac Mountains in Serbia, with molecular and ecological notes. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 212 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Projet d’élargissement à 2x3 voies de l’autoroute A4 sur le Contournement Nord-Est de Metz (CNEM) - Zones de présence d'espèces animales et végétales. 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 138 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 2560 records from Upper Silesian Museum, Bird Observations. 190 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 269 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 10 records from Molecular analysis of five controversial Balkanic species of Allolobophora (sensu lato) Eisen, 1873 (Lumbricidae, Clitellata) with emendation of the genus Cernosvitovia Omodeo, 1956. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 1 records from Redescription of Pterygoplichthys punctatus and description of a new species of Pterygoplichthys (Siluriformes: Loricariidae). 59 records from Artenvielfalt auf dem Schulgelände. 3889 records from Regroupement d'études et d'inventaires - Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 349 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 74 records from Données sur les Opisthobranches et Planaires de Mayotte. 2656 records from Waterbird counts, Luomus dataset. 234 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 12 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 69 records from BIRDRACE Pfeifenten. 3 records from Revision of the genus Lindholmiola HESSE, 1931 (Gastropoda: Pulmonata: Helicodontidae). 17 records from Marine metagenome ICM_JRV. 147 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 123 records from Ladybirds of Ireland. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 43 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 107 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 1585766 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 128 records from Rohrmeistereiplateau und angrenzendes Gebiet. 666 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 286 records from California State University, Long Beach Birds. 1926 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 1 records from Marine metagenome ICM_AWP. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 3640 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Regroupement d'études et inventaires - Données opportunistes sur les odonates. 123 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 16705 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2018. 284 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1461 records from Records of Halicarcinus planatus at sub-Antarctic regions. 620 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 3327 records from BioGIS - Mammals - SPNI. 1403 records from Amphibia and Reptilia (Luomus). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1 records from Diatom abundance of Hole 60-460. 6 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 1334 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 5861 records from MfN - Fossil vertebrates IV. 1 records from Review of the genus Mesosaimia Breuning with description of a new species (Coleoptera: Cerambycidae: Lamiinae: Mesosini). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 44358 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6301 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 97 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 14 records from Contribution à la connaissance des Orthoptères – Locusta - Données opportunistes de Benoit DUHAZE. 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 3529 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Alain BERLY. 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 196 records from A worldwide catalog of the Vermileonidae (Diptera: Brachycera). 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 191 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 255 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 12712 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 432 records from KUO Mollusca collections (KUO). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 9 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 423 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from Plan Aquitain d'Action Sonneur à ventre jaune - PRA Sonneur à ventre jaune - étude de répartition. 11555 records from Collection Crustacea - ZMB. 47 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Suivi Amphibiens dans le cadre du chantier. 740 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 1 records from Parc éolien d'Argillières - hérpétofaune. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 187 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 6 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 217 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 5 records from Warnowufer Groß Klein. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 18539 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 30 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 344 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 99 records from Extracellular DNA marine sediment Targeted Locus (Loci). 68 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 14 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LESSIEUR David. 57 records from Species inventories NP Öewersauer, Recorder-Lux Database. 78 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - FRAPNA74 - 24HNAT. 2 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 24490 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 2 records from Occurrence of mammalia relicts at site Igstadt I. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 12999 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 909 records from Butterfly Community of the Yuchi Tea Garden in 2019-2020. 727 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 6241 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 1192 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 150 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 15217 records from Collection Pisces SMF. 475 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 31638 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 302 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 65 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 14346 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 293 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 302766 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 163420 records from Arizona State University Hasbrouck Insect Collection. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 87899 records from MDFRC macroinvertebrate survey. 128 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des reptiles 2014. 590 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 11 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 8 records from A new species of Breviconia Conroy-Dalton & Huys, 2000 (Copepoda: Harpacticoida: Ancorabolidae Sars) from the Bering Sea, northern Pacific Ocean (Russia). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 5253 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 181199 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 172 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6763 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 514 records from BUND - Dassower See (Lübeck/Dassow). 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 63385 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur François FOURNIER. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Sächsische Schweiz (Wehlener Gebiet). 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 279 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 2545 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 804 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur JOURDE Rémi. 876 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 59 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 9084 records from WTSWW Data: All Taxa (West Wales). 11686 records from NCSM Mammalogy Collection. 3 records from Mise en oeuvre des mesures compensatoires à l'aménagement du parc photovoltaïque d'Hourtin - Données opportunistes. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 226 records from Nivå Bay species list, Zealand, Denmark. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 165529 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 798 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations d'odonates réalisées lors de journées de prospections animées par la LPO Aquitaine. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 2 records from Registros de una Tortuga carey (Eretmochelys imbricata) incautada y rehabilitada en el municipio de Riohacha. 10 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 6782 records from Odonata de Veracruz. 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 159 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Damien TROQUEREAU. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 6668 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 3932 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 79 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 84531 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 5 records from Pollen profile II/B at Krumbach, Germany. 26093 records from Weevil and Bark Beetle records via iRecord. 3 records from A new species of the genus Dugesia (Tricladida: Dugesiidae) from China. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 7 records from Nationalpark Harz Schul-AG Braunlage. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 58 records from Stigmella stettinensis (Nepticulidae) specimen data. 44 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 81 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 9 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 10810 records from NOAA’s National Coral Reef Monitoring Program Coral Benthic Assessment Data. 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 9 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 10 records from Revision of the maculate species of the Anthracus annamensis group from the East Palaearctic and Oriental Regions. Part 2. A redescription of Anthracus nesophilus (ANDREWES, 1936) and six new species from Nepal, India and SE Asia (Coleoptera, Carabidae, Harpalini, Stenolophina). 146 records from Plan de gestion 2016 - 2020 du site du coteau de Pinel (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 13 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 2776 records from Biodiversity of the Desna river valley and its tributaries. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 50 records from Reptiles de la Ecoreserva ASA (Meta, Acacías) - Proyecto FIBRAS. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 4 records from Loricifera - SMF. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 479121 records from KTP Ring Data. 123 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 583 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 18 records from Soil metagenome from healthy and unhealthy agricultural soil. 1478 records from Suivi des oiseaux de passage : programme FLASH - Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 41 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 58 records from Brown University Herbarium. 90 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 689 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 136791 records from Happywhale - Humpback Whale in North Pacific Ocean. 24 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" site de La Beute (Tosse). 695 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 36 records from The genus Hybos em> Meigen (Diptera: Empidoidea: Hybotidae) in Thailand strong> p>. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 51 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaires "Espaces Naturels Sensibles" du Luy (Saugnac-et-Cambran). 14 records from Réserves Naturelles de France (RNF) - RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 1 records from CEFS_16S_ITS. 11 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de Moliets, la Prade et Moïsan’ (FR7200717) - Inventaire et regroupement de données Natura 2000. 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 17 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent DUPRAT. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 1872 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 26185 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2 records from Suivi Cistude d'Europe du Bassin de stockage de Balanos - Données Cistude d'Europe du Bassin de stockage de Balanos. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 202 records from Schanzenanlage Bergham. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 160 records from AVJNF: Søholt Storskov, amphibian survey. 54 records from Taxonomic study of the genus Tenupalpa Lee et Li, 2021 (Lepidoptera: Gelechiidae Thiotrichinae) from China, with descriptions of fifteen new species. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 9098 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 72 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 19 records from Schulgelände SGD/Viersen. 1533 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 4 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 9384 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 168 records from Gerromorpha (Hemiptera: Heteroptera) from the Metropolitan Region of Santarém, Brazil, including three new species of Microvelia Westwood, 1834 (Veliidae: Microveliinae). 365 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 85 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 3 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 135 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faunistique de l'ENS des Parc des berges de Seine. 64 records from Bats of northeastern Vietnam. 214 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 13 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1560 records from Pacific turtle tracks: Turtle-Safe Seas Project. 1688 records from BenthosChukchiFN762_1976_Falk5. 60 records from Survey of Trogolaphysa Mills (Collembola, Paronellidae) of the Brazilian Amazon including five new species and the description of the dorsal chaetotaxy of the first instar. 42 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 33 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 65 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 10796 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 61 records from Knechtweide (Kohlfurth). 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 90 records from MCP-Mamiferos - Coleção de Mamíferos. 448 records from Benthic macrofauna abundance of sediment core 12930-073. 89 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 18 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 509 records from Occurrence database of native plants and animals of south-central Chile. 92 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Parc naturel régional de Lorraine. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 4 records from Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 24 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2271 records from Helmintos parásitos de peces del sureste de México. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Olivier LE GALL. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 1630 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 38 records from Happywhale - Killer Whale in Arctic Ocean. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 294 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Hubert GUIMIER. 1803 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection Rousset -1947-2013. 876 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 79 records from Réseau Loup - Lynx ONCFS - Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 100 records from Plan de gestion des Marais du Conseiller - Inventaire et suivi Rhopalocères – Protocole PROPAGE. 3167 records from Données DREAL Centre-Val de Loire - Faune - 2018. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 40263 records from A dataset of bird inventory records at Cloudbridge Nature Reserve, Talamanca Mountains, Costa Rica, between March 2016 and May 2020.. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 391 records from Artificial Cover Board Monitoring for Red-backed Salamander (Plethodon cinereus) at Marsh-Billings-Rockefeller NHP in Vermont, USA (1999-2000). 3109 records from Insectes Hyménoptères Scoliidés de France - Insectes Hyménoptères Scollidés de France. 84 records from Projets photovoltaïques de Sablirot Sud et Nord - Inventaires écologiques. 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Valentin LECONNET. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 31 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Stanislas WROZA. 3978 records from Weddell Sea macrozoobenthos EASIZ I. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 5398 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 12 records from A new species of the Nuneztovari Complex of Nyssorhynchus (Diptera: Culicidae) from the western Brazilian Amazon. 9 records from Occurrence of mammalia relicts at site Climauti II. 80 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 34 records from On some Moroccan Pamphagidae, with the description of a new species of Euryparyphes (Orthoptera: Caelifera). 43 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 50 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de NICOLAS Vincent (SAPROX). 6 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 3830 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Oiseaux PT - Inventaire non protocolé. 90 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 9 records from seawater metagenome Metagenome. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 4333 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 946 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 56 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 4054 records from Fish specimens of Toyama Science Museum. 119 records from Range table from ostracoda in ODP Hole 143-866B. 4653 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 99 records from Sonidos de la Ecoreserva Campo Rubiales (Puerto Gaitán, Meta) - Proyecto FIBRAS. 3529 records from A dataset from bottom trawl survey around Taiwan. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10629 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Marc GAGNE. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 150 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par la Réserve naturelle nationale de l'Étang Noir selon le protocole STELI adapté pour le programme. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 115 records from Strathclyde badger sett surveys 1996-2000. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 3507 records from Spider (NSMK-SP). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1318 records from Atlas des papillons de jour et des libellules du Languedoc-Roussillon - Données CEN L-R papillons/libellule. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 2 records from A new species of Pristimantis (Anura: Strabomantidae) with a colourful venter from the cloud forests of Colombian western Andes. 69 records from Nottekanal, Klasse 7 - 10. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 4 records from Parc éolien du Mont de Bagny II - Inventaire de la flore sur l'aire d'étude. 4704 records from Inventaire des Mollusques Sphaeriidae de France. 17048 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CORNIC Jean-François. 744 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3901 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 8 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 15 records from Flora und Fauna im Brexbachtal. 615 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 3238 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from Regroupement d'études et inventaires - Suivis botaniques. 16753 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 2086 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A mid-Cretaceous female scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) in Burmese amber. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 67 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 12 records from Lepidoptera specimen database of Japan. 7 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 121 records from BIRDRACE - The famous Grouse feat. The James. 85 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 57 records from Biota presente en el humedal laguna El Meridiano, departamento del Tolima. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 6 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 29 records from Occurrence of mammalia relicts at site Goyet Cave 3. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 10 records from Centrale Hydroélectrique de Bouginal. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 31 records from Two new Hottentotta species from Iran, with a review of Hottentotta saulcyi (Scorpiones: Buthidae). 12 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1249 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 23 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 58 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2985 records from Colección Entomológica CDMB. 6 records from NZCS Invertebrates New Collection After 1987. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 16929 records from Lepidoptera (Specimens NRM). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 1056 records from Community Foundation for Ireland Records. 164 records from Identification et caractérisation des peuplements entomologiques des landes - Inventaire Coléoptères. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 27799 records from Collection of saproxylic and xylobiont Beetles. 22124 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mikaël PAILLET. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4617 records from Données du Parc National de la Guadeloupe - Données de type contact en Guadeloupe. 11 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Charles BRESSON. 36 records from Inventaire en continu de la ZNIEFF 'Prairies Du Loubet Et Du Tolzac' - 720020107 - Prairies du Loubet et du Tolzac - Inventaire Oiseaux, Amphibiens & Reptiles opportunistes. 331 records from Projet éolien de Plestan II - Volet chiroptère/étude en altitude. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 47 records from Galls on Beech Trees in Hainich, 2008. 1000 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 4 records from The Chinese species of the mealybug genus Neotrionymus Borchsenius (Hemiptera: Coccoidea: Pseudococcidae). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 2 records from Développement du pôle commercial de Peyssilieu (Meyzieu 69) - Inventaire orthoptère_Meyzieu -pôle commercial de Peyssilieu. 350 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société Linnéenne de Maine-et-Loire. 1 records from Abrocomidae. 32 records from PROJET DE CENTRALE PHOTOVOLTAÏQUE SAINTE ANNE LA ROCHE SUR YON - Inventaire espèces presente sur site. 12331 records from Insectes Hétéroptères Mirides de France. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 23 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 135 (N.S) n° 28 (1), 2000 - Données faune. 355 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 114 records from Pollen analysis of sediment core GeoB6518-1. 2 records from Paralomis White, 1856 (Crustacea: Decapoda: Anomura) from India, with morphological variability in Paralomis indica Alcock & Anderson, 1899. 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 43 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 135 records from DIBA-Parc del Montnegre i el Corredor. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 4755 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 21 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 183719 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 2 records from On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov.. 7 records from Grundwasserlebensraum im Englischen Garten (München). 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 14400 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 2 records from Dilatapalochrus gen. nov. - a new species and a new genus of soft-winged flower beetle of the tribe Apalochrini (Coleoptera: Malachiidae) from East Africa. 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2873 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 720 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 42007 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pascal Dupont. 18 records from Système d'Information sur la Nature et les Paysages d'Ile de France - suivi du site Natura 2000 Carrière Saint Nicolas. 2170 records from Inventaire des sangsues du Nord-Ouest de la France - réalisation d'un guide à destination du grand public et des naturalistes - Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 38 records from Faunal assemblage of sediment core GS7603-13. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 10207 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2287 records from Colección de Anfibios. 1256 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Zootaxa. 10973 records from NBMB Herps. 1 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 10048 records from Index Site Surveys Data for Olympia Oysters, Ostrea lurida, in British Columbia – 2009 to 2017. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2617 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 383 records from NHMO DNA Bank Other groups collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 4 records from IMMS Ridley 9 (aggregated per 1-degree cell). 42 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 15 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (suivi par piège lumineux) réalisées par le CEN Aquitaine. 463 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 192291 records from University of Michigan Museum of Zoology, Division of Birds. 2823 records from Benthos Chirnov Basin 1986 and 2002. 6087 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 14 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 187 records from Abundance and habitat of echinoderms collected during the Bangor-Watamu Expedition in 1969. 1 records from Sherwood Arboretum Botanical Collection Dataset. 2 records from Plan de gestion 2015 - 2020 du site du site des zones humides du Mondarrain et de l'Artzamendi (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 127 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 1 records from Revision of the Neotropical scarab beetle genus Aegidiellus Paulian (Coleoptera: Scarabaeidae: Orphninae) with description of two new species. 9 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 209 records from Happywhale - Leopard seal in South Atlantic Ocean. 12 records from Analyses of the recent components of sediment core PS1219-1. 28 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Reptiles. 2 records from Transfer of Homalonychus raghavai Patel & Reddy, 1991 to Storenomorpha Simon 1884 (Araneae: Zodariidae). 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 75 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1 records from First record of the interaction between the arthropod-pathogenic fungus Gibellula and a new species of harvestman Auranus (Stygnidae) narrowly endemic to the Brazilian rain forest. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 186863 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 4 records from New Serphitidae and Gallorommatidae (Insecta: Hymenoptera: Microprocta) in the Early Cretaceous Lebanese amber. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 16253 records from Birds Specimens. 438 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 18843 records from DMNS Mammal Collection (Arctos). 133 records from Ecomorphology of the mangrove oyster Crassostrea cucullata in a mangrove swamp in Gazi (Kenya) in May 1991. 101 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivi Pics 2012 - Site Natura 2000 des Barthes de l'Adour. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 251 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de AUNEAU Florent. 1 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 1 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 394 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 70 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 10 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 11 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 48 records from Zoo Frankfurt. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 128 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from Pandanipora fragilis-a new deep-water cyclostome bryozoan from the subequatorial Mid-Atlantic Ridge, Atlantic Ocean, and a review of Pandanipora worldwide. 2 records from Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China. 277 records from Norfish: Shetland Cod Fishery 1520-1796. 738 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 47 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 421 records from Expedición ornitológica en los municipios de Florencia y Morelia, (Caquetá) - BIO Alas, cantos y colores. 1 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 149 records from Plan de gestion 2008 - 2012 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 622 records from Projet éolien de Lan Vraz - Volet avifaune, chiroptère (étude au sol), flore. 13 records from The genus Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Maranhão State, northeastern Brazil. 10 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 5 records from Collection Malakologie - SMNG. 1 records from Rocky-intertidal cheilostome bryozoans from the vicinity of the Sesoko Biological Station, west-central Okinawa, Japan. 1 records from Toxorhynchites (Lynchiella) caatingensis sp. nov. (Diptera: Culicidae) from the semi-arid region of Brazil. 315 records from Coastal and Marine Species Database. 535 records from Convention Fédération française de golf - MNHN 2016-2019. 124 records from NHMD Amber Collection. 164 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 18 records from Two new desma-less species of Theonella Gray, 1868 (Demospongiae: Astrophorida: Theonellidae), from the Great Barrier Reef, Australia, and a re-evaluation of one species assigned previously to Dercitus Gray, 1867. 7488 records from SILENE-FAUNE-PACA - Yoann_BLANCHON_2017_12_18. 322 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Marc CORAIL. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 1014 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 2 records from History of Life Exhibition. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 9 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Sophie COHEN. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 159 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 1852 records from Database of Australasian Vertebrate Occurrences. 123 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 748 records from Phenological Center - Birds (Laplandskiy). 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 18 records from Four Species of Dulichiidae (Crustacea: Amphipoda) from Japan, with the Description of a New Genus and Two New Species. 57 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 5430 records from Inventaires menés dans le cadre du Groupe Invertébrés de Midi-Pyrénées (GIMP) - Données invertébrés en Midi-Pyrénées. 13 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 112 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 29677 records from Marine Biological Sample Database, JAMSTEC. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 412 records from Otter (Lutra lutra), Outer Hebrides. 416 records from The Living Murray Fish data. 3 records from Urocleidoides spp. (Monogenea: Dactylogyridae) from the gills of Parodon nasus (Characiformes: Parodontidae) from a Brazilian stream with descriptions of two new species. 25974 records from Long-term Bird Census in Cigu 2004-2017. 14669 records from Species monitoring and inventories SICONA, Recorder-Lux database. 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 237 records from SILENE-FAUNE-PACA - BARTH-Environnement_2017_12_18. 367 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de HACALA Axel. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 251 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 5 records from New and little-known mute Trigonidiinae species from China (Orthoptera: Grylloidea: Trigonidiidae). 17 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 21 records from New State Records Of Kentucky (Usa) Stoneflies (Plecoptera). 1956 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 1286 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 2923 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 6 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de CLERGET sylvie. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 4 records from Stadtrandlandschaft Apolda-Nord. 40 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 29 records from Sea Turtles of Nicaragua's Pacific Coast (aggregated per 1-degree cell). 7 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 61547 records from Florida Keys Reef Visual Census 2010. 1288 records from annex1. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 349 records from PROJET EN FAVEUR DES HIRONDELLES 2018. 2 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 3 records from The King of the Dwarves: a new cryptic species of Dainty Frog (Anura: Pyxicephalidae: Cacosternum) from the eastern Great Escarpment of South Africa. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 14 records from AlgaTerra. 22572 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 1135 records from MfN - Fossil vertebrates III. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 165 records from HSU Vertebrate Museum Mammals Collection. 30 records from Revision and phylogeny of the genus Andocaeculus (Acari: Caeculidae) I: the A. weyrauchi species group. 10 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 3 records from A new species of the southern Central American genus Linoderus Sharp (Coleoptera: Staphylinidae: Staphylininae) with a revised key and an updated phylogeny. 224 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Informatisation des carnets de terrain de Georges Catherine. 21338 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 13 records from North Cyprus 2015 - Green Turtles (aggregated per 1-degree cell). 40 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 26117 records from UTEP Insects (Arctos). 1 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DURON Cyril. 4 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 40 records from Elaboration du DOCOB du site Natura 2000 ‘Marais du Bas Médoc’ (FR7200680) - Inventaire Faune. 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 24 records from Plan de gestion 2006 - 2010 du site du site du domaine de Rodié (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 248 records from Registros de arañas en el marco del proyecto: Influencia de la dieta sobre la toxinología y toxicología en arañas. 1 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 1550 records from Biodiversidad asociada al proyecto Línea de Transmisión a 110 kV San Lorenzo-Sonsón. 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 688 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 79758 records from natagora-earlybirds. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 44 records from W.E.B. Parc éolien des vents du Serein - Insectes - Inventaire non standardisé. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 43 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 370 records from Qweeds - Queensland. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 2 records from Two new species of Bucculatrix Zeller from southeast China (Lepidoptera: Bucculatricidae). 5543 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude écologique du Parc des Lilas (94). 2814 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données bibliographiques AsFrA. 1 records from Acropoma profundum, a New Species of Lanternbelly (Teleostei: Perciformes: Acropomatidae) from the Solomon Islands. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 170 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 87 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1 records from Louisiana State University, Shirley C. Tucker Herbarium - Lichens. 61 records from A taxonomic study on the South Korean Diplonevra (Diptera: Phoridae). 4 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 7 records from N.C.W. Beadle Herbarium (NE) AVH data. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 270 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 30 records from Schulgelände (Wetter). 88 records from Deponie Klausdorf. 16 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 247 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 1982 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 4923 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 14 records from A study on the genus Anaches Pascoe, 1865 (Coleoptera, Cerambycidae, Lamiinae Pteropliini), with a new species and two new synonyms. 1484 records from Population research on small rodents (Rodentia) and shrews (Soricidae) in Steinkjer Municipality – Norway; 1996 - 2017 based on systematic catches with ordinary mouse traps in traplines. 2486 records from BioGIS - Reptiles - HUJ collections. 12 records from Analyses of the recent components of sediment core PS1222-1. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200664 - Coteaux calcaires de la vallée de la Dordogne (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 271 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 5 records from Projet de port de plaisance de Brétignolles sur Mer - Mammifères - Inventaire non protocolé. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 43 records from Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific. 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 217 records from Étude préalable à la création d’une Réserve Naturelle Régionale des landes périgourdines menée par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 124 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 756 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 1786 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 23 records from Description of eight new species of Otacilia Thorell, 1897 from southern China (Araneae: Phrurolithidae). 1 records from The first complete specimen of the deep-water shrimp Batella praecipua De Grave 2004 (Crustacea: Decapoda: Alpheidae). 165 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 10 records from Ostracoda abundance of Hole 32-306. 3281 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1 records from Morphological and molecular evidence of a new species of Melanochlamys (Gastropoda: Heterobranchia) from the Bohai Sea, China. 262 records from Centrale solaire Zac de l'Empereur - Etude d'Impact Données Faune/Flore. 66002 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27190 records from Formidabel; Belgian Ants Database. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 700 records from 2013_nsmk_smpl_in. 119 records from Suivis des sites gérés par la Fédération des Chasseurs des Landes - Suivi des leucorrines sur le site du Marais du Plata. 9 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 4 records from Laminatubus (Serpulidae, Annelida) from eastern Pacific hydrothermal vents and methane seeps, with description of two new species. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Stéphane DULAU DULAU. 146 records from Abundance of birds in the Lena Delta Region. 1 records from First report of Cleruchoides Lin & Huber (Hymenoptera: Mymaridae) from the Oriental region with description of a new species from India. 150 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 7 records from Descriptions Of The Adult Male And Female Genitalia Of The Genus Osobenus Ricker (Plecoptera: Perlodidae). 5 records from Plan de gestion 2007 - 2011 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 44 records from Plan de gestion 2011 - 2015 du site du domaine de Rodié (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 69 records from artsprosjektet_48-13_monomyx. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 5360 records from Colección Ornitológica de la Universidad del Valle. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1668 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 28 records from Inventaire Chiroptères sur le site du Roc Branlant - Inventaire et suivi Chiroptères. 178 records from Données du Sanctuaire AGOA issues de l'agence de Aires marines protégées - Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 167 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de JORIGNE Bastien. 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 333 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Renaud PUISSAUVE. 1013 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Stanislas WROZA. 627 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 9 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1700 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 94 records from Truppenübungsplatz Panzerkaserne Böblingen. 619 records from Base BOMBINA du Parc Naturel régional Lorraine - Réseaux écologiques/Trame verte et bleue. 2 records from Additions to the deep-sea echiuran (Echiura) fauna of the North-East Atlantic. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 1 records from Revision of theGonioctena flavoplagiata species-group (Coleoptera: Chrysomelidae: Chrysomelinae), with descriptions of two new species from China and Laos. 12487 records from Florida Keys Reef Visual Census 1996. 12 records from Regroupement d'études et inventaires - Régulation espèces invasives. 18 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 236280 records from Wild bees of Belgium. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 55 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 20 records from 2019_nsmk_smpl_mm_20. 1 records from Taxonomic position of the genus Sassanidotus Farzanpay, 1987 (Scorpiones: Buthidae). 8 records from Study on the genus Morimospasma Ganglbauer, 1889 (Coleoptera, Cerambycidae Lamiinae) from Hubei, China. 9740 records from Royal British Columbia Museum Entomology Collection. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 9 records from Notes on Scaphisoma of Kalimantan (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from A new species of Macrothrix (Crustacea, Branchiopoda, Macrothricidae) from the Neotropics with description of the marthae-group. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 66 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 6 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 4 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 852 records from Données de l'Observatoire des Mammifères marins de l'Archipel Guadeloupéen - Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 221 records from Acoustic detections from R/V Song of the Whale during the spring 2019 MAPS survey (NMFS permit 14809). 493 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 90 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 3, 1992. 3 records from Taxonomic noteson thegenusPseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae Eumeninae) from Vietnam with key to all known species in the Oriental region. 361 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 6 records from Pollen and spore abundance of Hole 42-381. 23 records from 2017 Onwards Rare Invertebrates in the Cairngorms Northern Silver Stiletto Fly Survey Data. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 42 records from 76 - Bois de Beaumont - Chiroptères. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 1 records from Regroupement d'études et inventaires - Mortalité lignes HT. 45 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 14 records from Diversity and distribution of North Atlantic Lepechinellidae (Amphipoda: Crustacea). 176 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 160 records from Seabird sightings in Ghana and Ivorycoast. 71 records from Avifauna asociada al área boscosa del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 1441 records from Cowan Tetrapod Collection - Herpetology. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 36215 records from Royal Belgian Institute of Natural Sciences Mammal collection. 11 records from Hemmerder Schelk (Unna). 84 records from Shellfish (MNHM-MS). 12 records from Atlas des oiseaux nicheurs de France réalisés par carte IGN50 - Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 30998 records from Elephant Seal Sightings, Macquarie Island. 411 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 3 records from Systematics and convergent evolution in three Australian genera of Pepsinae spider wasps (Hymenoptera: Pompilidae). 2829 records from Clare Biological Records Centre Dataset 2004-2007. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 2 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 3 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 1554 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 20 records from Truchas Mexicanas. 13282 records from Senckenberg - CeDAMar Resource. 1 records from Endogean and Cavernicolous Coleoptera of the Balkans. XXIII. A new species of Paramaurops J. Müller (Coleoptera: Staphylinidae: Pselaphinae) from Greece. 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 466 records from Inventaire dans le cadre des missions Natura 2000 - Données Faune. 93 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 94 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 2793 records from Oiseaux des jardins - Inventaire indépendant de FrédérIc Revers. 330 records from Benthic macrofauna abundance of sediment core 13200-045. 1 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 509 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 39 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 1 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 80 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 7 records from Insect specimens of Himeji City Science Museum. 2221 records from Ohio University Invertebrate Paleontology Collection. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 1 records from Description of the female of Chelis ferghana Dubatolov, 1988, an endemic moth species of the Tien Shan Range in Central Asia (Lepidoptera: Erebidae Arctiinae). 28 records from Occurrence of mammalia relicts at site Bettelküche. 1 records from A new Himalayan species of Alfieriella (Coleoptera: Cryptophagidae). 1 records from Fish specimens of Natural History Museum, Kishiwada City. 345 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 150 records from Registros de Nerita fulgurans asociados a microplasticos en las playas de Santa Marta y Puebloviejo. 2326 records from DEMNA-DNE : Freshwater mussels occurrences in Wallonia. 5 records from Labiobaetis Novikova & Kluge in West Africa (Ephemeroptera, Baetidae), with description of a new species. 12 records from Naturerfahrung. 9 records from The plant bug subfamily Phylinae in Japan, with key to genera and descriptions of eight new species (Hemiptera: Heteroptera: Miridae). 936 records from Données naturalistes de Damien Combrisson. 68 records from Synopsis of the Asian species in the genus Zarcosia Collado & Alonso-Zarazaga 1996 with new combinations and descriptions of fourteen new species. 19 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Suivi des reptiles des landes du Technopôle du Madrillet. 1 records from Across the great divide: revision of the genus Eupetaurus (Sciuridae: Pteromyini), the woolly flying squirrels of the Himalayan region, with the description of two new species. 4462 records from Insectes Hyménoptères Formicidés de Corse. 547 records from RMT Trawl catch from the 2003/04 V3 BROKE-West voyage. 28 records from Mollusques continentaux de France - Données malacologiques du site Natura 2000 de Cessière-Montbavin. 3456 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 224 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 2 records from A New Iranian Species Of The Subgenus Labidostoma (Prostigmata: Labidostomatidae), With New Biogeographic Data On The Integrum Species Group. 3 records from A review of the Barsine perpallida-B. yuennanensis species-group, with descriptions of six new species (Lepidoptera: Erebidae: Arctiinae). 448 records from Benthic macrofauna abundance of sediment core 13078-013. 1 records from The Notched-frons Katydids of Kashmir (Jammu and Kashmir) India: new records and a new species of Euconocephalus (Tettigoniidae: Conocephalinae Copiphorini). 2 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 832 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 29 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 3 records from A new species of Aphantolana Moore & Brusca, 2003 (Crustacea: Isopoda Cirolanidae) from the Andaman Islands, northern Indian Ocean. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 257 records from Données espèces Expertise IQE 311. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 4 records from Amphilochidae *. 1 records from Tyrannosaurus rex from the McRae Formation (Lancian, Upper Cretaceous), Elephant Butte Reservoir, Sierra County, New Mexico. 15130 records from MMS Surveys, SCB 1995-1997. 3 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 64154 records from India Biodiversity Portal publication grade dataset. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 142 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3083 records from Butterflies of Singapore and Peninsular Malaysia (Lycaenidae). 736772 records from Oiseaux de France métropolitaine en hiver 1977-1981. 56 records from Pollen counts of sediment core GeoB9503-5. 191 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 266 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 40 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 3 records from A new species of Cyrtodactylus Gray (Squamata; Gekkonidae) from the Thai Highlands with a discussion on the evolution of habitat preference. 272828 records from SILENE-FAUNE-PACA - Parc_National_de_Port_Cros_2017_12_18. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 31 records from The genus Coenosia Meigen in Iran, with a key to species and description of a new species (Diptera: Muscidae). 427 records from Zooplankton community and pelagic copepods in Tudor creek (Mombasa, Kenya) between 1984 and 1987. 20887 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 438 records from Vermont Freshwater Mussel Atlas 1995. 3886 records from Colección Carcinológica de Yucatán. 22 records from Satellite Tracking of Hawksbill Turtles in Melaka, Malaysia (aggregated per 1-degree cell). 115 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 86 records from Etude avifaunistique de la LPO Limousin sur les landes haut-viennoises - Inventaire et suivi Avifaune de la lande de Beaubreuil. 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 1 records from The genus Mytilina in China, with description of a new species (Rotifera: Monogononta: Mytilinidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 160 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" de Bas-Rouge (SAINT-MICHEL-ESCALUS). 86 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 488 records from Biotope cadastre of the open landscapes, Recorder-Lux database. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 29 records from Données espèces - Expertise IPE 70. 7207 records from Colección Entomológica Universidad Nacional de Colombia, Sede Palmira (CEUNP). 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 3 records from A new species of snail-eating snakes of the genus Pareas Wagler, 1830 (Reptilia: Serpentes) from eastern Himalayas, India. 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 224 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 103 records from Bat diversity data by Formosan Golden Bat's Home. 1 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from Iran. 222 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 5 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Camille GAUTIER. 46 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 1457 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre-Yves GOURVIL. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 415 records from Seasonal fluctuation of the meiobenthos community in Avicennia marina mangrove sediments at Gazi Bay (Kenya) between 1992 and 1993. 12 records from Plan de gestion 2019 - 2023 du site du coteau de Lembeye (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1024 records from Inventaires complémentaires des espèces déterminantes ZNIEFF - Données naturalistes sur des périmètres pour créations de nouvelles ZNIEFF ou atualisation de ZNIEFF existantes. 858 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 1 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 10 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 230 records from Porifera diversity and distribution data in the Southern Gulf of Mexico. 1 records from Description on Solitudes dushengi gen. et sp. nov. from Xinjiang, China (Araneae: Gnaphosidae). 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 4070 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 12 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 3618 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 20 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 27 records from A revision of the African wolf spider genus Amblyothele Simon. 23 records from A review of Paratranes Zimmerman, 1994, Xanthorrhoea-associated weevils of the Tranes group (Coleoptera, Curculionidae, Molytinae), with description of a new species. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 11 records from Two new remarkable and endangered catfish species of the genus Cambeva (Siluriformes, Trichomycteridae) from southern Brazil. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 84979 records from NINA Vanndata fisk. 94 records from Mammals (UWEP-MM). 1 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 7 records from Liogenys Guerin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae Diplotaxini) of northern South America and Central America: taxonomic overview with four new species. 510 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Inventaires des cygnes du département de l'Eure. 2 records from Teaching Collection. 25 records from Herpetofauna de la expedición P
Keywords: GBIF; biodiversity; species occurrences